The moderating role of Al-Falah values in the effect of digital marketing and product innovation on the competitive advantage of micro, small, and medium enterprises in Sinjai Regency - selmiana salam; Sudriman; Syaharuddin; Supriadi; Kamaruddin Arsyad (LP2M IAIN Palopo, 2026)
This study aims to examine the effects of digital marketing adaptation and product innovation on the competitive advantage of micro, small, and medium enterprises (MSMEs) in Sinjai Regency, Indonesia, and to investigate the moderating role of Al-Falah values. A quantitative approach was employed using a survey method involving 220 MSME owners. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4.0. The results indicate that digital marketing adaptation has a positive and significant effect on competitive advantage (β = 0.215; p < 0.05), while product innovation shows a stronger positive effect (β = 0.355; p < 0.05). Al-Falah values also have a positive and significant direct effect on competitive advantage (β = 0.325; p < 0.05). The structural model demonstrates strong predictive power, with an R² value of 0.712, indicating that 71.2% of the variance in competitive advantage is explained by the proposed model. However, the moderating effects of Al-Falah values on the relationship between digital marketing adaptation and competitive advantage (β = −0.014; p > 0.05), as well as between product innovation and competitive advantage (β = −0.020; p > 0.05), are not statistically significant. These findings suggest that digital marketing adaptation and product innovation independently enhance MSMEs’ competitive advantage, while Al-Falah values primarily function as an ethical foundation rather than a reinforcing moderator. This study contributes to the literature by integrating Islamic ethical values into a digital competitiveness framework and offers practical implications for strengthening sustainable MSME competitiveness.